2011
DOI: 10.1371/journal.pgen.1002234
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Host Molecular Responses Differentiate Symptomatic and Asymptomatic Influenza A Infection

Abstract: Exposure to influenza viruses is necessary, but not sufficient, for healthy human hosts to develop symptomatic illness. The host response is an important determinant of disease progression. In order to delineate host molecular responses that differentiate symptomatic and asymptomatic Influenza A infection, we inoculated 17 healthy adults with live influenza (H3N2/Wisconsin) and examined changes in host peripheral blood gene expression at 16 timepoints over 132 hours. Here we present distinct transcriptional dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
235
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(248 citation statements)
references
References 74 publications
13
235
0
Order By: Relevance
“…48 Even in patients with mild illness, elevated cytokine levels distinguish between those who develop symptoms and those who have asymptomatic infection. 49 Few people with fatal influenza die during the first few days of illness when a proinflammatory response dominates. Instead, like patients with sepsis, 50 most die during the second week or later when an antiinflammatory response and immunosuppression become dominant and virus replication has decreased.…”
Section: The Host Response To Influenzamentioning
confidence: 99%
“…48 Even in patients with mild illness, elevated cytokine levels distinguish between those who develop symptoms and those who have asymptomatic infection. 49 Few people with fatal influenza die during the first few days of illness when a proinflammatory response dominates. Instead, like patients with sepsis, 50 most die during the second week or later when an antiinflammatory response and immunosuppression become dominant and virus replication has decreased.…”
Section: The Host Response To Influenzamentioning
confidence: 99%
“…Let SNR, h and d be the true model parameters as defined in Section II. Then, assuming (7), as p n , n → ∞,…”
Section: Statistics Of the Misaligned Covariancementioning
confidence: 99%
“…and: → denotes almost sure convergence, w = v 1 (Σ (τ )), and c is defined in (7). Here, γ is the gain/loss due to misalignments (i.e.…”
Section: Statistics Of the Misaligned Covariancementioning
confidence: 99%
See 1 more Smart Citation
“…Biological response signals detected in peripheral blood can reliably distinguish between noninfectious conditions and infection with a virus, bacteria or fungus in adult and pediatric populations, in both experimental infectious challenge settings and communityacquired infection. Recently, we demonstrated that RNA-based biomarkers developed in a human influenza challenge study could classify influenza-infected patients from healthy controls with 100% accuracy and from bacterial causes with 93% accuracy [15,16]. When an RT-PCR version of the test was evaluated in a cohort of subjects presenting to the emergency room with microbiologically confirmed respiratory or systemic infection, performance was preserved (sensitivity of 89% and specificity of 94%) [17].…”
mentioning
confidence: 99%